Some Approximations to the Distribution of Econometric Criteria which are Asymptotically Distributed as Chi-Squared - Sargan, J. D. (Econometrica, 1980)
[This paper is concerned with giving general conditions for the validity of a approximation to a distribution function by means of the weighted sum of a set of Chi-squared distribution functions. The conditions are very similar to those of [3]. The approximation is illustrated by an example of its use.]